Peningkatan Kreativitas Melalui Pelatihan Finger Painting Bagi Guru PAUD - Rista Sundari; Fatimatuz Zahro (Journal of Early Childhood and Character Education, 2021)
Creativity is a very important aspect for everyone because with creativity everyone can express ideas and solve problems creatively. The purpose of the preparation of this research is for PAUD teachers to be able to increase creativity in early childhood learning, especially through finger painting practice training. The research method used is a library research method with data collection techniques from several sources and relevant literature accompanied by content analysis. Teachers are required not only to produce good learning in transforming science but also to hone the potential that exists in students. The results showed that with the training, there were many benefits or advantages obtained by teachers as educators to be able to carry out the teaching and learning process creatively, innovatively, and potentially.